Використання синонімів та антонімів на заняттях з англійської мови - Петровська, Надія Максимівна; Petrovska, N. M. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті підкреслено важливість ефективних методів викладання іноземної мови, зокрема, використання синонімів та антонімів. Систематизовано та узагальнено теоретичний та практичний матеріал з проблеми, що досліджується. Описано методику роботи з синонімами та антонімами англійської мови. Подано конкретні лексичні одиниці, які найчастіше вживаються під час занять. Доведено ефективність роботи з синонімами та антонімами за допомогою тестових завдань. Вживання синонімів/антонімів англійської мови допомагає збага¬тити лексичний запас студентів, підвищує інтерес до дисципліни, що вивчається, сприяє найбільш повному досягненню комплексної мети – формуванню комунікативних навичок. The article deals with effective methods of teaching foreign languages, in particular with usage of synonyms and antonyms. The aim of the article is the creation of conditions for formation of communicative skills at the English lessons. The task of the investigation is to analyze and to prove scientifically the methods of work in the branch of synonymy and antonymy. Theoretical and practical material on the problem is systematized. The methods of work with synonyms and antonyms are described. The concrete lexical units most widely used at the lessons are given The effectiveness of work with synonyms and antonyms using tests is proved. The usage of synonyms/antonyms helps to enrich students’ vocabulary, raise their interest to the subject they study, promotes the achievement of the main goal – the formation of communicative skills.
Usage of Synonyms and Antonyms at the English Lessons
Keywords: ефективний метод; effective method; комунікативні навички; communicative skills; синоніми; synonyms